The Impact of Workplace Discipline and Motivation on Employee Performance in Improving Organizational Success - Uki Yonda Asepta; Ivan Widjaja; Sopiah Sopiah; Ludi Wishnu Wardana (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
In a more competitive business environment, employee performance is a crucial factor that influences an organization's success. Elevated employee performance not only facilitates the attainment of business objectives but also fosters a positive and productive work environment. This study seeks to examine the correlation among employee motivation, work discipline, and performance, along with external influences that may affect the interplay among these three components. By comprehending this link, it is anticipated that firms can devise more effective strategies for managing human resources, hence enhancing total employee performance. This study used a quantitative methodology with a sample of all employees from energy companies in Madura, comprising a total of 50 individuals. Data were gathered via questionnaires with a Likert scale ranging from 1 to 5. Data study employed multiple linear regression, revealing that job motivation and work discipline significantly influenced employee performance. The analysis results indicated that the regression model accounted for 44.1% of the variance in employee performance, with work motivation and work discipline identified as significant independent factors. This study's conclusions offer theoretical and practical insights for firms to enhance employee performance. Organizations must cultivate a work environment that fosters internal drive and work discipline, while also considering external elements such as effective supervision and leadership structures. Consequently, firms can formulate more efficient human resource management strategies to enhance employee performance across diverse sectors.